Management of extensive portal vein thrombosis via thrombolysis and thrombectomy without underlying liver disease: A case report - Mohammadshah Isam Gul (14777947) (2024)
Key Clinical Message Portal vein thrombosis (PVT) is a rare condition, particularly in non‐cirrhotic patients. Anticoagulation remains the mainstay of the treatment. Extensive PVT can lead to variceal bleeding, ascites, bowel ischemia, and hypersplenism. The role of thrombolysis and thrombectomy in these patients remains unclear. However, there is evidence that local thrombolysis and thrombectomy should be considered in those who remain symptomatic on anticoagulation and are at risk of complications with acute PVT. Other Information Published in: Clinical Case Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/ccr3.8920